Empirical Analysis of Financial and Non-Financial Risks of the Commercial Bank - Tsintsadze, Asie; Glonti, Vladimer; Oniani, Lela; Ghoghoberidze, Tamar (European Journal of Sustainable Development, 2019)
Background: Activities of commercial banks are connected with numerous risks, the source of which is the internal and external processes of the bank. Objectives: Risk management science has been studying the origins of the risks, determining their impact quality and avoiding expected loss models from the 1950s. Method/Approach: Credit risk regressive analysis is based on the selection of effective factors, determination of their influence and prediction of future according to the correlation coefficient. Results/Findings: In the article, it is discussed the regressive analysis of operational risk. Conclusion: The effect of credit and operational risks on the financial results of the Bank is based on the results obtained and recommendations have been developed to increase risk management efficiency. Keywords: credit risk, operational risk, regressive analysis, risk management, forecasting.